Effects of fatique on movement variability during stretchshortening cycle - Edwards, S.; Steele, J.; Cook, J.; Purdam, C.; McGhee, D. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Although lower limb injury has been linked to fatigue, it is unknown whether movement variability may act as a protective mechanism, possibly reducing the risk of an athlete developing an overuse injury. Therefore, the aim of this study was to establish the effects of fatigue on movement variability during the stretch-shortening cycle. Thirteen male athletes performed a submaximal stretch-shortening cycle (SSC) fatigue protocol, with three-dimensional kinematic and kinetic recorded for each participant`s lower limbs. When fatigued, athletes substantially increased their movement variability, whilst maintaining similar kinematics compared to when non-fatigued, suggesting that athletes with flexible motor behaviours and adaptability increase their movement variability when fatigued and, in turn, may decrease their risk of a developing an overuse injury.